Start me up! : the no-business-plan business plan - Eka, Ebong (Career Press, 2014)
There are four major pitfalls that business owners experience that inevitably lead to failure. Start Me Up! provides strategies to avoid those pitfalls and gives you the powerful ideas you need to build your thriving business. This is the perfect time to start a small business using your existing skills. Although far too many small businesses fail in their first year, many such failures are absolutely preventable. Ebong Eka will show you how to not just survive, but thrive in your new venture. In Start Me Up!, you'll learn how to: -Discard inferior business ideas before you invest your time and money in them -Simplify your viable business ideas and accurately identify the best markets to target -Charge your customers higher prices without losing them -Avoid wasting time on mindless tasks so you can focus on running your business -Create brand ambassadors, engage customers, and grow your sales -- all while spending less money! The best and most successful companies know the importance of the Four S's: structure, strategy, systems, and sales. Most companies that fail, lack one or more of these necessary factors. Let Ebong show you how to be one of the former.